Cellular therapies in organ transplantation - Hoogduijn, MJ; Issa, F; Casiraghi, F; Reinders, MEJ (Wiley, 2021)
Cellular therapy is a promising tool for improving the outcome of organ transplantation. Various cell types with different immunoregulatory and regenerative properties may find application for specific transplant rejection or injury‐related indications. The current era is crucial for the development of cellular therapies. Preclinical models have demonstrated the feasibility of efficacious cell therapy in transplantation, early clinical trials have shown safety of several of these therapies, and the first steps towards efficacy studies in humans have been made. In this review, we address the current state of the art of cellular therapies in clinical transplantation and discuss monitoring tools and endpoints for these studies.